Primary extraskeletal osteosarcoma of the esophagus with PPM1D-BCAS3 fusion: a case report and literature review - Luo, Shuai; Tian, Xiaoxue; Xu, Ting; Ji, Qing; Li, Yao; Wang, Jinjing (Frontiers in Medicine, 2025)
BackgroundExtraskeletal osteosarcoma (ESOS), a malignant soft tissue neoplasm characterized by the presence of osteoid or cartilage matrix, arises without bone involvement. ESOS within the esophagus is particularly rare. This study reported a case of esophageal ESOS with PPM1D-BCAS3 fusion, offering an analysis of its clinicopathological features and a comprehensive literature review aimed at advancing the diagnostic understanding of clinical pathologists.Case demonstrationA 76-year-old male presented with a 2-month history of subxiphoid pain and dysphagia. Chest computed tomography CT revealed irregular mid-esophageal wall thickening and luminal stenosis, raising suspicion for mid-esophageal carcinoma. Painless endoscopic ultrasonography detected a hypoechoic intraluminal esophageal mass. Endoscopic submucosal dissection (ESD) and histopathological analysis confirmed primary ESOS of the mid-esophagus. No adjuvant therapy was administered postoperatively. However, the patient experienced a recurrence with multiple metastases 9-months later.ConclusionThe diagnosis of esophageal ESOS, a condition of exceptional rarity, necessitates an integrative evaluation that encompasses clinical history, imaging modalities, and histopathological analysis, with a critical distinction from metastatic osteosarcoma and carcinosarcoma. This study presented the first case of esophageal ESOS with PPM1D-BCAS3 fusion treated via ESD, providing a significant point of reference for clinicians and pathologists. The management of ESOS demands vigilant monitoring and precise follow-up care.